The Implementation of Philosophical Values of the Merdeka Curriculum in Shaping Students’ Character in Islamic Religious Education At Primary Schools - Linda Linda; Abu Mansur; Nyayu Soraya (Papanda Publisher, 2026)
This study aims to analyze the implementation of philosophical values in the Merdeka Curriculum on the character formation of students related to Islamic Religious Education (PAI) subjects in Elementary Schools in Pampangan District, Ogan Komering Ilir Regency. The merdeka curriculum is present as a new paradigm in the world of Indonesian education that emphasizes freedom of learning, character strengthening, and the holistic development of student potential. The subject of Islamic religious education (PAI) has a strategic role in the internalization of philosophical values originating from Islamic teaching and noble values. This research utilized a qualitative methodology, specifically a case study approach, with school principals, Islamic education teachers, and students from SD Negeri 1 Secondong, SD Negeri 1 Serimenang, SD Negeri 1 Pampangan and SD Negeri 2 Pampangan serving as the study’s subjects. This study employed interviews, observations, and documentation as data collection instruments, which were subsequently analyzed using Miles & Huberman’s theoretical framework. The research results show that the philosophical values of the Merdeka Curriculum, such as religious values, humanism, freedom and responsibility, and mutual cooperation, have been implemented Islamic Education (PAI) learning through lesson planning, contextual learning strategies, and teacher role models. The implementation of these values has a positive impact on the formation of student character, particularly in religious attitudes, discipline, responsibility, tolerance, and noble morals. However, there are still obstacles such as limited supporting facilities and differences in student background. Therefore, synergy is needed between schools, teacher, and parents to optimize the implementation of the philosophical values of the Merdeka Curriculum in Islamic Education (PAI) learning to strengthen the character of students in elementary schools.